“I Learned to Let Go of My Pain”. The Effects of Mindfulness Meditation on Adolescents with Chronic Pain: An Analysis of Participants’ Treatment Experience - Danielle Ruskin (Children, 2017)
Chronic pain can lead to significant negative outcomes across many areas of life. Recently, mindfulness-based interventions (MBIs) have been identified as potentially effective tools for improved pain management among adolescents living with pain. This study aimed to explore the experience of adolescents who participated in an eight-week mindfulness group adapted for adolescents with chronic pain (MBI-A), and obtain their feedback and suggestions on group structure and content. A mixed method design was used employing qualitative data from focus groups and data from a satisfaction questionnaire. Focus group data were transcribed and analyzed using inductive simple descriptive content analysis. Of the total participants (n = 21), 90% (n = 19) provided feedback by completing satisfaction questionnaires and seventeen (n = 17) of those also participated across two focus groups. Analysis of the focus group transcripts uncovered six themes: mindfulness skills, supportive environment, group exercises (likes and dislikes), empowerment, program expectations, and logistics. Participants reported positive experiences in the MBI-A program, including support received from peers and mindfulness skills, including present moment awareness, pain acceptance, and emotion regulation. Group members suggested increasing the number of sessions and being clearer at outset regarding a focus on reduction of emotional suffering rather than physical pain.